2000
DOI: 10.1128/aac.44.2.316-319.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regional Prophylaxis with Teicoplanin in Monolateral or Bilateral Total Knee Replacement: an Open Study

Abstract: , patients undergoing primary elective monolateral or bilateral total knee replacement (TKR) were consecutively enrolled in a prospective, open clinical study on the efficacy and safety of regional prophylaxis with teicoplanin (TEC). Those scheduled for monolateral TKR (115 patients) received 400 mg of TEC in 100 ml of saline as a 5-min infusion into a foot vein of the leg to be operated on immediately after the tourniquet was inflated to 400 mm Hg (ca. 50 kPa). For patients undergoing bilateral surgery (45 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…Tissue samples (skin, subcutaneous tissue, bone, synovium) 2-10 times higher through regional route de Lalla et al [9] Clinical study 160 patients (205 knees) undergoing TKA, 400 mg teicoplanin through the foot vein…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue samples (skin, subcutaneous tissue, bone, synovium) 2-10 times higher through regional route de Lalla et al [9] Clinical study 160 patients (205 knees) undergoing TKA, 400 mg teicoplanin through the foot vein…”
Section: Authorsmentioning
confidence: 99%
“…Some authors have used a foot vein cannula for administering prophylactic antibiotics in TKA. With this approach, substantially higher tissue concentrations of antibiotic can be achieved at the surgical site without systemic side effects [8,9,15,17] (Table 1). However, cannulation of a foot vein is difficult, time-consuming, and may compromise sterility.…”
Section: Introductionmentioning
confidence: 99%
“…Regional administration utilising a tourniquet has been suggested [7], and performing this via the intraosseous route is currently under investigation. The advantages of regional administration include reducing systemic drug concentrations and side effects while achieving higher tissue concentrations at the operative site.…”
Section: Introductionmentioning
confidence: 99%
“…Yamashita et al [4]suggested that complete eradication of MRSA is necessary to treat MRSA-associated glomerulonephritis, and if this is not attained, permanent loss of renal function may occur. Many investigators have examined the clinical efficacy of teicoplanin given daily for treatment of MRSA infection [5, 6]. Extracorporeal blood purification therapies represent a promising new approach to the adjuvant treatment of sepsis and systemic inflammation [7].…”
Section: Introductionmentioning
confidence: 99%